MANAGEMENT OF A PATIENT WITH FRUIT BLADDER IN ISTHMIC-CERVICAL INSUFFICIENCY (CLINICAL CASE) - Сергей Валерьевич Рыбников; Артем Константинович Неретин; Елена Владимировна Рудаева; Игорь Вадимович Пачгин; Вадим Гельевич Мозес; Светлана Ивановна Елгина; Анастасия Михайловна Ошлыкова (The Publishing House Medicine and Enlightenment, 2021)
According to various authors, isthmic-cervical insufficiency (ICI) occurs in 40 % of very early and early preterm births. The effectiveness of various methods for correcting ischemic-cervical insufficiency is widely discussed. Micronized progesterone, obstetric pessary, surgical correction of ICI are used. The surgical technique of correction has more than half a century of history with mixed results. According to various authors, when the fetal bladder prolapses in patients with isthymic-cervical insufficiency, surgical correction allows the pregnancy to be prolonged by 10 weeks or more in comparison with conservative treatment methods.